Optimization of Volume and Mass of Eggshell in Removal of Linear Alkylbenzene Sulfonate Levels in Laundry Waste - Pinarti, Inggis; Noorbilqis, Fitri; Pratiwi, Sani Widyastuti; Nurmalasari, Ratna (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Linear alkylbenzene sulfonate (LAS) is one of the most common anionic surfactants in synthetic detergent formulation. Being a component of domestic waste, LAS can potentially cause environmental damage. Detergent wastewater that contains LAS needs to be properly treated before being released into the environment. This study aims to treat the laundry waste by using thermally activated chicken eggshell adsorbent. The steps carried out in this study were the preparation of adsorbents, quality test of adsorbents produced, testing of adsorbent on used laundry waste based on reducing concentration of LAS and testing of the Langmuir adsorption equation and the Freundlich adsorption equation. Adsorption process of LAS observed variations in adsorbent mass are 4g, 8g, 12 g, and 16 g, and variations in the sample volume used in this experiment are 50 ml, 100 ml, 150 ml, and 200 ml. Stirring time is 60 minutes. The filtrate was analyzed to determine the concentration of LAS. The obtained results indicate that the optimum mass of adsorbent is 12 grams with a sample volume of 50 ml. This adsorption condition resulted in Linear Alkylbenzene Sulfonate levels of 3,376 ppm, which can reduce LAS levels by 69.86%, with an adsorption capacity of 0.2997 mg/g. Based on the result of this study, LAS adsorption follows the Langmuir isotherm equation, with a coefficient of determination (R2) greater than that of the Freundlich isotherm, which is 0.9977. This equation indicates that the adsorption process that occurs is chemisorption. The use of thermally activated chicken eggshell as an adsorbent can be an alternative, environmentally friendly waste processing technique.